DADAR: Duplicate Address Detection using ARP in Mobile Ad Hoc Network (MANET) - Victor Rajan, K; Rhymend Uthariaraj, V (International Journal of Computer Sciences and Engineering, 2020)
Mobile Ad Hoc Network (MANET) is infrastructure free, highly dynamic wireless network, where central administration or configuration by an administrator is very difficult. In contrast to infrastructure based network, MANET supports autonomous and spontaneous networking and thus should be capable of self-organization and configuration. This self-configuring network allows the nodes to automatically configure addresses and routes based on ongoing traffic. Due to the distributed and dynamic nature of MANETs, centralized servers like DHCP cannot be used to assign IP address to nodes. In this paper we present a novel approach DADAR, for the efficient duplicate address detection and auto configuration of nodes in a MANET. Special features of DADAR are the support for frequent network partitioning and merging and very low protocol overhead. Nodes choose initial address using random numbers. Duplicate Address Detection (DAD) algorithm resolves the address conflict which can occur due to partitioning or merging. We are devising a novel approach to detect duplicate address using Address Resolution Protocol. ARP messages are sent by nodes to translate IP address to Hardware address. ARP packets contain the IP address and Hardware address pair of the nodes. These packets are analyzed in the background to identify duplicate addresses and conflicts are resolved. This approach does not introduce any new protocol or packet format.